THE ROLE OF INNOVATIVE PEDAGOGICAL SOFTWARE TOOLS IN IMPROVING THE EFFECTIVENESS OF TRADITIONAL EDUCATION - Karimov , Yusuf; Sodiqjonov , Yaxyobek; Jumanov , Anvar (MMIT Proceedings, 2023)
This work discusses the benefits and achievements of using Phet pedagogical software tools produced by scientists from the University of Colorado. Using modern information technologies in educational processes, it is understood that special software tools in the organization of classes, computer modeling of physical and mathematical processes, the creation of an immitation computer model of a real physical process, the basics of NNG. As well as the specific important aspects of modeling, the conditions for the preparation of various physical devices and instruments, the description of phenomena in a lively and natural way, the possibility of repeating the experiment any time at little opportunity, the ability to also demonstrate processes that are difficult to observe or cannot be observed at all. These pedagogical software tools allow the teacher to demonstrate many physical effects on a computer monitor as well as to improve a new type of non-traditional teaching using a multimedia projector.